COMPLEX RESEARCH OF THE SPUTUM IN NEWLY DIAGNOSED PATIENTS WITH PULMONARY TUBERCULOSIS USING POLYMERASE CHAIN REACTION AND MYCROBIOLOGICAL CONTROL OF THE VIABILITY OF MYCOBACTERIUM TUBERCULOSIS - E.V. DUDENKO; S. SYDYKOVA (Avicenna Tajik State Medical University, 2019)
Objective: The use of polymerase chain reaction (PCR) in a comprehensive study of sputum in newly diagnosed patients with pulmonary tuberculosis (PTB) in the control of mycobacterium tuberculosis (MTB) viability by the microbiological method. Methods: The object of the study - 59 newly diagnosed patients with PTB in admission for treatment and 28 patients with PTB two months after the start of anti-tuberculosis chemotherapy. The study material is the sputum of PTB patients. Identification of the dead and persistent MTB was noted with the positive result of PCR (PCR+) and the absence of growth of MTB on the dense of nutritional environment of Levenstein-Jensen. The DNASorb-B and Litekh sets were used for DNA extraction of Mycobacterium tuberculosis complex. For amplification, Politub and AmpliSens MBT kits were used. Detection of amplification products was carried out with electrophoresis in 1.7% agarose gel in the presence of bromide ethidium Results: Before treatment, PCR was detected in 52 (88.1%) of the 59 PTB patients examined, 34 (57.6%) tested positive for inoculation (culture+). 25 (42.4%) of patients, lack of growth of MTB out of 59 PTB patients. After 2 months of chemotherapy, PCR+ was detected in 23 (82.1%) out of 28 patients with PTB, culture+ - in 13 (46.4%), no growth of MTB was revealed in 15 (53.6%). Conclusion: Before treatment, PCR was detected in 52 (88.1%) of the 59 PTB patients examined, 34 (57.6%) tested positive for inoculation (culture+). 25 (42.4%) of patients, lack of growth of MTB out of 59 PTB patients. After 2 months of chemotherapy, PCR+ was detected in 23 (82.1%) out of 28 patients with PTB, culture+ - in 13 (46.4%), no growth of MTB was revealed in 15 (53.6%).